EKSPLORASI GERAKAN TARI DENGAN BUDAYA TRADISIONAL KOMPANGAN DALAM PELESTARIAN BUDAYA MELAYU JAMBI - Sasabillah; Rohmah , Nisa Nur; Novi, Desita; Qibtiah, Maria; Marcellia, Giska; Ashari, Rahmat; Mawaddah, Egi Amaza; Butarbutar, Ririn; Rahmani, Resya; Sasmita, Cici; Fitriyani, Nuramna; Rajagukguk, Rut Putri; Ananta, Viola; Saputra, Hardian; Perangin-angin, Romian; Nurhalisa, Intan; Desita Nova (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research discusses the importance of preserving regional culture as the identity of the Indonesian nation in the midst of globalization challenges. The main focus is on a variety of traditional arts and cultures such as dance, regional music, traditional clothing, and traditional musical instruments from various regions of Indonesia. The study also highlights the efforts that have been made to preserve regional culture, such as cultural arts education in schools, participation in art competitions, and the role of family and community. This research aims to foster the awareness of the younger generation of the nation's cultural wealth and encourage the preservation of cultural heritage so that it does not become extinct in the future. Keywords: cultural arts, preservation, regional culture